Microfluidic devices for small‐angle neutron scattering. Issue 3 (5th June 2018) - Lopez, Carlos G.; Watanabe, Takaichi; Adamo, Marco; Martel, Anne; Porcar, Lionel; Cabral, João T.
Abstract : A review of materials and fabrication methods provides recommendations for microdevices for small‐angle neutron scattering. Abstract : A comparative examination is presented of materials and approaches for the fabrication of microfluidic devices for small‐angle neutron scattering (SANS). Representative inorganic glasses, metals, and polymer materials and devices are evaluated under typical SANS configurations. Performance criteria include neutron absorption, scattering background and activation, as well as spatial resolution, chemical compatibility and pressure resistance, and also cost, durability and manufacturability. Closed‐face polymer photolithography between boron‐free glass (or quartz) plates emerges as an attractive approach for rapidly prototyped microfluidic SANS devices, with transmissions up to ∼98% and background similar to a standard liquid cell ( I ≃ 10 −3  cm −1 ). For applications requiring higher durability and/or chemical, thermal and pressure resistance, sintered or etched boron‐free glass and silicon devices offer superior performance, at the expense of various fabrication requirements, and are increasingly available commercially.